2008
DOI: 10.1111/j.1365-2133.2008.08678.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of categories at risk for high quality of life impairment in patients with vitiligo

Abstract: Detailed information on QoL in patients with vitiligo may lead dermatologists to pay particular attention to patient categories at risk for a high QoL impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
118
4
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 28 publications
7
118
4
6
Order By: Relevance
“…Although vitiligo does not result in any restrictions on life expectancy or a patient's capacity to work, it can cause cosmetic disfigurement and may affect the psychological well being of patients 1,2 . The etiology of vitiligo remains unclear, but oxidative stress and the accumulation of free radicals have been proposed as important pathogenic mechanisms [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Although vitiligo does not result in any restrictions on life expectancy or a patient's capacity to work, it can cause cosmetic disfigurement and may affect the psychological well being of patients 1,2 . The etiology of vitiligo remains unclear, but oxidative stress and the accumulation of free radicals have been proposed as important pathogenic mechanisms [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Sampogna et al [6] have reported significant correlation between quality of life levels and depressive symptoms and alexithymia. Unlike many other medical conditions, skin disorders are easily noticed by other people.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many other medical conditions, skin disorders are easily noticed by other people. Even though vitiligo does not directly cause a physical distress, it might cause discomfort as it disrupts the physical appearance and affects the psyche in a very negative way [6,40]. Studies in this field indicate that patients with vitiligo might experience low self-esteem [23] and depression [6,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects approximately 1 to 2% of the It represents a heavy (4,5). The people may suffer related social and emotional consequences (6).…”
mentioning
confidence: 99%